Aggregation Scheme with Secure Hierarchical Clustering for Wireless Sensor Networks - Su, Tung-Shih; Huang, Mei-Wen; Li, Wei-Shou; Hsieh, Wen-Shyong (International journal of distributed sensor networks, 2012)
In a large-scale wireless sensor network, a topology is needed to gather state-based data from sensor network and efficiently aggregate the data given the requirements of balanced load, minimal energy consumption, and prolonged network lifetime. In this study, we proposed a ring-based hierarchical clustering scheme (RHC) consisting of four phases: predeployment, parent-child relationship building, deployment, and member join phases. Two node types are distributed throughout the network: cluster head nodes (type 1 node) and general sensor nodes (type 2 node). The type 1 node has better battery life, software capability, and hardware features than the type 2 node; therefore, the type 1 node is a better cluster head than type 2 node. Due to our IP naming rules and type 1 nodes as cluster heads, public key cryptography, such as RSA (Rivest, Shamir, Adleman), or ECC (Elliptic Curve Cryptosystem), is easily implanted to our system to strengthen our security. The sink node is the only certification authority in our system, but n level cluster heads can be extended to n level certification authorities if needed, where n is maximum number of level.